2014
DOI: 10.4049/jimmunol.1401244
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 Fate Reporter Reveals Origin and Control of IL-22 Production in Homeostasis and Infection

Abstract: Interleukin 22 (IL-22) is a cytokine that regulates tissue homeostasis at barrier surfaces. A variety of IL-22 producing cell types are known, but identification on the single cell level remains difficult. We therefore generated a fate reporter mouse that would allow the identification of IL-22 producing cells and their fate mapping in vivo. To trace IL-22 expressing cells, a sequence encoding Cre recombinase was cloned into the Il22 locus and Il22Cre mice were crossed with reporter mice expressing enhanced ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 37 publications
10
93
0
1
Order By: Relevance
“…IL-22 signalling restores barrier function during inflammation and its protective role for the gut mucosa has also been demonstrated in mouse models of colitis. In the intestine, IL-22 promotes wound healing, tissue regeneration, and epithelial cell proliferation [106,107]. It regulates epithelial-microbial homeostasis through the induction in IECs of anti-microbial peptides, specifically of the Reg family, including RegIIIβ and RegIIIγ, as well as β-Defensin 2 and β-Defensin 3 [103,108].…”
Section: Il-22 and Gut Homeostasismentioning
confidence: 99%
“…IL-22 signalling restores barrier function during inflammation and its protective role for the gut mucosa has also been demonstrated in mouse models of colitis. In the intestine, IL-22 promotes wound healing, tissue regeneration, and epithelial cell proliferation [106,107]. It regulates epithelial-microbial homeostasis through the induction in IECs of anti-microbial peptides, specifically of the Reg family, including RegIIIβ and RegIIIγ, as well as β-Defensin 2 and β-Defensin 3 [103,108].…”
Section: Il-22 and Gut Homeostasismentioning
confidence: 99%
“…Thus, IL‐22 appears as a crucial host‐derived factor modulating susceptibility to GVHD (Figure 2). The known cellular sources of IL‐22 are T cells and ILC3 and very recently an IL‐22 reporter mouse revealed that the major and most stable IL‐22‐producing cells are the NKp46 − CD4 − ILC3, while only a minority of NKp46 + ILC3 expressed IL‐22 35. In line with these recent findings, only IL‐22 produced by the IL‐23‐responsive RORγt + CCR6 + NKp46 − ILC3 proved to be essential in the protection against GVHD 9.…”
Section: Potential Of Il‐22 Producing Ilc3 In Gvhd Therapymentioning
confidence: 99%
“…Reprogramming between distinct CD4 + T cell subsets can be observed in human and mouse T cells under certain conditions in vitro [16][17][18][19] or in mice in vivo on transferring highly purified popu lations of cells [20][21][22][23][24][25] . By using lineage-tracing systems in mice, in which cells are engineered to express Cre recombinase under the control of transcriptional elements that regulate key polarization factors (such as cytokines or transcription factors) and a fluorescent protein reporter of Cre activity, endogenously polarized CD4 + T cells from many subsets have been found to change phenotype during their lifespan [26][27][28][29] . In humans, the combination of pheno typic analyses and sequencing of T cell receptors (TCRs), which act as unique barcodes for each T cell, has made it possible to investigate the phenotype of clonal descendants of single cells.…”
mentioning
confidence: 99%